Contribution of serum lipids and cholesterol cellular metabolism in lung cancer development and progression - Hartmann, Philipp; Trufa, Denis; Hohenberger, Katja; Tausche, Patrick; Trump, Sonja; Mittler, Susanne; Geppert, Carol-Immanuel; Rieker, Ralf; Schieweck, Oliver; Sirbu, Horia; Hartmann, Arndt; Neurath-Finotto, Susetta (Scientific Reports, 2023)
Neoplasms of the lungs are the leading cause of cancer incidence and mortality worldwide. Although immunotherapy has increased the overall survival of patients with lung cancer, there is the need to improve this treatment. At this regard, blood lipid levels are thought to be linked to cancer risk and thus a preventive intervention through regulation of the nutrition of patients with lung cancer is gaining much attention. In this study, we therefore asked about the contribution of serum lipids and cholesterol cellular metabolism in lung cancer development and progression. We measured different serum lipids and analyzed cholesterol synthesis enzymes 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR) and acetyl-coenzyme A cholesterol acetyltransferase 1 (ACAT1) as well as the cholesterol cellular export protein ATP-binding cassette (ABC) A-1 mRNA by quantitative PCR (qPCR) in the control and tumoral regions of post-surgery lung tissues to analyze the accumulation of cholesterol in cancer cells in a cohort of patients with lung adenocarcinoma (LUAD). We found that triglycerides in serum directly correlated with the body mass index (BMI) in patients with LUAD. By contrast, we found that high-density lipoprotein (HDL) cholesterol inversely correlated with the BMI, C-reactive protein (CRP) and overall survival and total cholesterol inversely correlated with the tumor diameter, serum CRP and overall survival in these LUAD patients. Functionally, the role of cholesterol is indispensable for the growth and development of normal animal cells where it is tightly regulated. Excess of cellular cholesterol regulated by HMGCR is converted to cholesteryl esters by the enzyme ACAT1 and exported extracellularly by the cholesterol transporter ABCA1. Here we found HMGCR and ACAT1 upregulated and ABCA1 downregulated in the lung's tumoral region of our LUAD cohort, indicating cholesterol dysregulated cellular export in lung tumor cells.
CRIS-Team Scopus Importer:2023-04-21

Effects of glucose concentration in the tumor microenvironment on Non Small Lung Cancer (NSCLC) Progression - Gähler, Alexander; Hohenberger, Katja; Tausche, Patrick; Chiriac, Mircea-Teodor; Rauh, Manfred; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Neurath-Finotto, Susetta (JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03

Enhanced Acid Sphingomyelinase Activity Drives Immune Evasion and Tumor Growth in Non-Small Cell Lung Carcinoma - Kachler, Katerina; Bailer, Maximilian; Heim, Lisanne; Schumacher, Fabian; Reichel, Martin; Holzinger, Corinna D.; Trump, Sonja; Mittler, Susanne; Monti, Juliana; Trufa, Denis; Rieker, Ralf; Hartmann, Arndt; et al. (Cancer Research, 2017)
The lipid hydrolase enzyme acid sphingomyelinase (ASM) is required for the conversion of the lipid cell membrane component sphingomyelin into ceramide. In cancer cells, ASM-mediated ceramide production is important for apoptosis, cell proliferation, and immune modulation, highlighting ASM as a potential multimodal therapeutic target. In this study, we demonstrate elevated ASM activity in the lung tumor environment and blood serum of patients with non-small cell lung cancer (NSCLC). RNAi-mediated attenuation of SMPD1 in human NSCLC cells rendered them resistant to serum starvation-induced apoptosis. In a murine model of lung adenocarcinoma, ASM deficiency reduced tumor development in a manner associated with significant enhancement of Th1-mediated and cytotoxic T-cell-mediated antitumor immunity. Our findings indicate that targeting ASM in NSCLC can act by tumor cell-intrinsic and -extrinsic mechanisms to suppress tumor cell growth, most notably by enabling an effective antitumor immune response by the host. Cancer Res; 77(21); 5963-76. ©2017 AACR.
EVALuna2:4034

FAM13A is associated with non-small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival - Eisenhut, Felix; Heim, Lisanne; Trump, Sonja; Mittler, Susanne; Sopel, Nina; Andreev, Katerina; Ferrazzi, Fulvia; Ekici, Arif Bülent; Rieker, Ralf; Springel, Rebekka; Assmann, Vera Elisabeth; Lechmann, Matthias; et al. (OncoImmunology, 2017)
Genome-wide association studies (GWAS) associated Family with sequence similarity 13, member A (FAM13A) with non-small cell lung cancer (NSCLC) occurrence. Here, we found increased numbers of FAM13A protein expressing cells in the tumoral region of lung tissues from a cohort of patients with NSCLC. Moreover, FAM13A inversely correlated with CTLA4 but directly correlated with HIF1? levels in the control region of these patients. Consistently, FAM13A RhoGAP was found to be associated with T cell effector molecules like HIF1? and Tbet and was downregulated in immunosuppressive CD4(+)CD25(+)Foxp3(+)CTLA4(+) T cells. TGF?, a tumor suppressor factor, as well as siRNA to FAM13A, suppressed both isoforms of FAM13A and inhibited tumor cell proliferation. RNA-Seq analysis confirmed this finding. Moreover, siRNA to FAM13A induced TGF? levels. Finally, in experimental tumor cell migration, FAM13A was induced and TGF? accelerated this process by inducing cell migration, HIF1?, and the FAM13A RhoGAP isoform. Furthermore, siRNA to FAM13A inhibited tumor cell proliferation and induced cell migration without affecting HIF1?. In conclusion, FAM13A is involved in tumor cell proliferation and downstream of TGF? and HIF1?, FAM13A RhoGAP is associated with Th1 gene expression and lung tumor cell migration. These findings identify FAM13A as key regulator of NSCLC growth and progression.
EVALuna2:6835

Glucose-Restricted Diet Regulates the Tumor Immune Microenvironment and Prevents Tumor Growth in Lung Adenocarcinoma - Gähler, Alexander; Trufa, Denis; Chiriac, Mircea-Teodor; Tausche, Patrick; Hohenberger, Katja; Brunst, Ann-Kathrin; Rauh, Manfred; Geppert, Carol-Immanuel; Rieker, Ralf; Krammer, Susanne; Leberle, Anna; Neurath, Markus; et al. (Frontiers in Oncology, 2022)
BackgroundLung cancer is the second common cancer type in western countries and has a high mortality. During the development and progression of the tumor, the nutrients in its environment play a central role. The tumor cells depend crucially on glucose metabolism and uptake. Tumor cell metabolism is dominated by the Warburg effect, where tumor cells produce large amounts of lactate from pyruvate under aerobic conditions. We thus reasoned that, reducing carbohydrates in the diet might support anti-tumoral effects of current immunotherapy and additionally target tumor immune escape. ObjectivesThe link between reducing carbohydrates to improve current immunotherapy is not clear. We thus aimed at analyzing the effects of different glucose levels on the tumor development, progression and the anti-tumoral immune response. MethodsWe correlated the clinical parameters of our LUAD cohort with different metabolic markers. Additionally, we performed cell culture experiments with A549 tumor cell line under different glucose levels. Lastly, we investigated the effect of low and high carbohydrate diet in an experimental murine model of lung cancer on the tumor progression and different immune subsets. ResultsHere we found a positive correlation between the body mass index (BMI), blood glucose levels, reduced overall survival (OS) and the expression of Insulin-like growth factor-1 receptor (IGF1R) in the lung tumoral region of patients with lung adenocarcinoma (LUAD). Furthermore, increasing extracellular glucose induced IGF1R expression in A549 LUAD cells. Functional studies in a murine model of LUAD demonstrated that, glucose restricted diet resulted in decreased tumor load in vivo. This finding was associated with increased presence of lung infiltrating cytotoxic CD8+ T effector memory (TEM), tissue resident memory T (TRM) and natural killer cells as well as reduced IGFR mRNA expression, suggesting that glucose restriction regulates lung immunity in the tumor microenvironment. ConclusionsThese results indicate that, glucose restricted diet improves lung immune responses of the host and suppresses tumor growth in experimental lung adenocarcinoma. As glucose levels in LUAD patients were negatively correlated to postoperative survival rates, glucose-restricted diet emerges as therapeutic avenue for patients with LUAD.
CRIS-Team WoS Importer:2022-05-27

IL-2 decreased PU.1 and PD-1 expression in NK-cells in NSCLC patients - Hohenberger, Katja; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Neurath-Finotto, Susetta (JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03

IL-9 Producing Tumor-Infiltrating Lymphocytes and Treg Subsets Drive Immune Escape of Tumor Cells in Non-Small Cell Lung Cancer - Heim, Lisanne; Yang, Zuqin; Tausche, Patrick; Hohenberger, Katja; Chiriac, Mircea-Teodor; Kölle, Julia; Geppert, Carol-Immanuel; Kachler, Katerina; Miksch, Sarah; Graser, Anna; Friedrich, Juliane; Kharwadkar, Rakshin; et al. (Frontiers in Immunology, 2022)
Although lung cancer is the leading cause of cancer deaths worldwide, the mechanisms how lung cancer cells evade the immune system remain incompletely understood. Here, we discovered IL-9-dependent signaling mechanisms that drive immune evasion in non-small cell lung cancer (NSCLC). We found increased IL-9 and IL-21 production by T cells in the tumoral region of the lung of patients with NSCLC, suggesting the presence of Th9 cells in the lung tumor microenvironment. Moreover, we noted IL-9 producing Tregs in NSCLC. IL-9 target cells in NSCLC consisted of IL-9R+ tumor cells and tumor-infiltrating lymphocytes. In two murine experimental models of NSCLC, and in vitro, IL-9 prevented cell death and controlled growth of lung adenocarcinoma cells. Targeted deletion of IL-9 resulted in successful lung tumor rejection in vivo associated with an induction of IL-21 and reduction of Treg cells. Finally, anti-IL-9 antibody immunotherapy resulted in suppression of tumor development even in established experimental NSCLC and was associated with reduced IL-10 production in the lung. In conclusion, our findings indicate that IL-9 drives immune escape of lung tumor cells via effects on tumor cell survival and tumor infiltrating T cells. Thus, strategies blocking IL-9 emerge as a new approach for clinical therapy of lung cancer.
CRIS-Team Scopus Importer:2022-05-20
Keywords: IL-9; immune escape; NSCLC; TIL; tumor immunotherapy

Impaired T-bet-pSTAT1? and perforin-mediated immune responses in the tumoral region of lung adenocarcinoma - Andreev, Katerina; Trufa, Denis; Siegemund, Raphaela; Rieker, Ralf; Hartmann, Arndt; Schmidt, Joachim; Sirbu, Horia; Finotto, Susetta (British Journal of Cancer, 2015)
In spite of modern therapies for non-small-cell lung cancer (NSCLC), prognosis for many patients is still poor and survival rates are low. Immunotherapy is the possibility to improve the lung immune response surrounding the tumour. However, this approach requires detailed understanding of the local immune-responses of NSCLC patients.We analysed samples from three different regions within the lungs of NSCLC patients, whereas we distinguished between patients suffering from adenocarcinoma and squamous cell carcinoma. Expression of type 1 T helper (Th1)/type 1 cytotoxic (Tc1) factors was assessed by quantitative real-time PCR, western blot analyses or immunohistochemistry. Cytotoxic cell activity of CD8(+) T cells was determined via co-culture with autologous tumour cells and apoptosis assay.We found decreased levels of the transcription factor T-box expressed in T cells (T-bet or Tbx21) and of the downstream activated IFN-?-dependent pSTAT1? isoform in the lung tumour areas of patients with NSCLC as compared with tumour-free control regions. In these patients, reduced T-bet and pSTAT1? levels were found associated with increased immunosuppressive markers like cytotoxic T lymphocyte-associated protein 4, programmed cell death 1 and with a suppression of the Th1 cell cytokine production and Tc1 cell activity.These findings confirm a central role of T-bet in targeted immunotherapy for patients with NSCLC.
EVALuna2:6728

Increased expression of the immunosuppressive interleukin-35 in patients with non-small cell lung cancer - Heim, Lisanne; Kachler, Katerina; Siegmund, Raphaela; Trufa, Denis; Mittler, Susanne; Geppert, Carol-Immanuel; Friedrich, Juliane; Rieker, Ralf; Sirbu, Horia; Finotto, Susetta (British Journal of Cancer, 2019)
Background: The immunosuppressive role of the cytokine IL-35 in patients with non-small cell lung cancer (NSCLC) is poorly understood. In this study, we analysed the localisation and regulation of IL-35 in the lung of patients with non-small cell lung cancer (NSCLC) to further elucidate the immune-escape of cancer cells in perioperative course of disease. Methods: Interleukin 35 (IL-35) was measured by ELISA in postoperative serum from 7 patients with NSCLC as well as 8 samples from healthy controls. Immunohistochemistry, FACS analysis, real-time PCR, as well as western blot from samples of the control (CTR), peri-tumoural (PT) and the tumoural (TU) region of the lung derived from patients with NSCLC and 10 controls were performed. Results: Here we found elevated levels of IL-35 in the TU region as well as postoperative serum from patients with lung adenocarcinoma. Consistently, we found an increased expression of IL-35 + Foxp-3 + cells, which associated with ARG1 mRNA expression and decreased TNFA in the TU region of the lung of patients with NSCLC as compared to their CTR region. Furthermore, in the CTR region of the lung of patients with NSCLC, CD68 + macrophages were induced and correlated with IL-35 + cells. Finally, IL-35 positively correlated with TTF-1 + PD-L1 + cells in the TU region of NSCLC patients. Conclusions: Induced IL-35 + Foxp3 + cell numbers in the TU region of the lung of patients with NSCLC associated with ARG1 mRNA expression and with TTF-1 + PD-L1 + cells. In the tumour-free CTR area, IL-35 correlated with CD68 + macrophages. Thus inhibitors to IL-35 would probably succeed in combination with antibodies against immune checkpoints like PD-L1 and PD-1 currently used against NSCLC because they would inhibit immunosuppressive macrophages and T regulatory cells while promoting T cell-mediated anti-tumoural immune responses in the microenvironment as well as the TU region of NSCLC patients.
CRIS-Team Scopus Importer:2019-05-10

Increased expression of the Th17-IL-6R/pSTAT3/BATF/Ror?T-axis in the tumoural region of adenocarcinoma as compared to squamous cell carcinoma of the lung - Balabko, Liubov; Andreev, Katerina; Burmann, Nadine; Schubert, Melanie; Mathews, Martina; Trufa, Denis; Reppert, Sarah; Rau, Tilmann; Schicht, Martin; Sirbu, Horia; Hartmann, Arndt; Finotto, Susetta (Scientific Reports, 2014)
Here we describe increased expression of IL6R in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to squamous cell lung carcinoma. Moreover, here we found increased IL6R in the tumour free part of the lung. By using a murine model of lung adenocarcinoma, we discovered that few lung tumour cells expressed IL-6R and CD4+CD25+Foxp-3+ T regulatory cells down-regulated IL-6R in the tumour bearing lungs. Downstream of IL-6R, the Th17 lineage-specification factors: Signal transducer and activator of transcription 3 (STAT3), Basic leucine zipper transcription factor, BATF and a protein encoded by the RORC in human (RAR-related orphan receptor C) (ROR?T), were also found induced in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to those carrying squamous cell carcinoma. Moreover, pSTAT3 protein was found phosphorylated and auto-phosphorylated in the tumoural region of patients with adeno cell carcinoma of the lung as compared to the tumoural region of patients with squamous cell carcinoma of the lung. Intranasal application of anti-IL-6R antibodies in a murine model of lung adenocarcinoma, induced T regulatory cell markers such as Foxp3, Ctla4, Icos, Il10, Il21, Folr4 and Lag3 and inhibited Rorc in lung adenocarcinoma.
EVALuna2:4416

Interleukin-10-regulated tumour tolerance in non-small cell lung cancer - Vahl, Julius Malte; Friedrich, Juliane; Mittler, Susanne; Trump, Sonja; Heim, Lisanne; Kachler, Katerina; Balabko, Liubov; Fuhrich, Nicole; Geppert, Carol-Immanuel; Trufa, Denis; Sopel, Nina; Rieker, Ralf; et al. (British Journal of Cancer, 2017)
Lung cancer is the most life-threatening cancer type worldwide. Treatment options include surgery, radio- and chemotherapy, as well as the use of immunomodulatory antibodies. Interleukin (IL)-10 is an immunosuppressive cytokine involved in tumour immune escape.Immunohistochemistry (IHC) on human lung surgery tissue as well as human tumour cell line cultures, FACS analysis, real-time PCR and experimental lung cancer.Here we discovered a positive correlation between IL-10 and IL-10 receptor (IL-10R) expression in the lung with tumour diameter in patients with lung cancer (non-small cell lung cancer), the most life-threatening cancer type worldwide. IL-10 and IL-10R were found induced in cells surrounding the lung tumour cells, and IL-10R was mainly expressed on the surface of Foxp-3(+) T-regulatory lymphocytes infiltrating the tumour of these patients where its expression inversely correlated with programmed cell death 1. These findings were confirmed in translational studies. In a human lung adenocarcinoma cell line, IL-10R was found induced under metabolic restrictions present during tumour growth, whereby IL-10 inhibited PDL1 and tumour cell apoptosis.These new findings suggest that IL-10 counteracts IFN-? effects on PD1/PDL1 pathway, resulting in possible resistance of the tumour to anti-PD1/PDL1 immunotherapy.British Journal of Cancer advance online publication 10 October 2017 doi:10.1038/bjc.2017.336 www.bjcancer.com.
EVALuna2:6915

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Late Breaking Abstract - Induction of the transcriptional repressor B lymphocytes-induced maturation protein-1 (Blimp-1) in lung cancer - Neurath, Laura; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Finotto, Susetta (EUROPEAN RESPIRATORY JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Lung tumor immune evasion mechanism in Non-small cell lung cancer (NSCLC) targets pSTAT5 in CD4+CD25+FoxP3-T effector cells - Tausche, Patrick; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Neurath-Finotto, Susetta (JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03

Management of the Expected Difficult Airway with Planned One-Lung Ventilation: A Retrospective Analysis of 44 Cases - Irouschek, Andrea; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Trufa, Denis; Sirbu, Horia; Golditz, Tobias (Thoracic and Cardiovascular Surgeon, 2024)
Background Difficult airway management is essential in anesthesia practice. Particular challenges are posed to patients who require intraoperative one-lung ventilation. Specific guidelines for these scenarios have been lacking. The recent update of German guidelines incorporates recommendations for securing the airway in anticipated difficult airway scenarios in patients requiring one-lung ventilation. However, scientific data on this specific topic is rare. Methods A retrospective analysis was conducted on adult patients undergoing thoracic surgery with one-lung ventilation from 2016 to 2021. During these years, the standard of practice has been in line with the now published guidelines. Patients with anticipated difficult airways were identified, and airway management strategies were analyzed. Results Among 3,197 anesthetic procedures, 44 cases involved anticipated difficult airways, primarily due to prior head and neck tumor treatment. Nasal bronchoscopic awake intubation followed by oral reintubation under videolaryngoscopic inspection and the use of bronchial blockers was the standard procedure. No severe complications were recorded, and one-lung ventilation was maintained successfully in all cases. Discussion The study highlights the challenges of managing difficult airways during thoracic surgery. Recommendations align with recent guidelines, emphasizing the importance of tailored approaches. The use of single-lumen tubes with bronchial blockers appears favorable over double-lumen tubes, offering comparable ventilation quality with reduced risks. Conclusion Despite limitations, the study underscores the safety and efficacy of tailored airway management strategies during one-lung ventilation in patients with anticipated difficult airways. The presented approach offers patient safety and practicability. Further multicenter studies are warranted to validate these findings and refine clinical approaches.
CRIS-Team Scopus Importer:2024-11-29
Keywords: airway (includes related subject matter); anesthesia (includes related subject matter); practice guidelines; thoracoscopy/VATS; ventilation

NFATc1 Promotes Antitumoral Effector Functions and Memory CD8+ T-cell Differentiation during Non-Small Cell Lung Cancer Development - Heim, Lisanne; Friedrich, Juliane; Engelhardt, Marina; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia; Finotto, Susetta (Cancer Research, 2018)
Nuclear factor of activated T cells 1 (NFATc1) is a transcription factor activated by T-cell receptor (TCR) and Ca2+ signaling that affects T-cell activation and effector function. Upon tumor antigen challenge, TCR and calcium-release-activated channels are induced, promoting NFAT dephosphorylation and translocation into the nucleus. In this study, we report a progressive decrease of NFATc1 in lung tumor tissue and in tumor-infiltrating lymphocytes (TIL) of patients suffering from advanced-stage non-small cell lung cancer (NSCLC). Mice harboring conditionally inactivated NFATc1 in T cells (NFATc1ΔCD4) showed increased lung tumor growth associated with impaired T-cell activation and function. Furthermore, in the absence of NFATc1, reduced IL2 influenced the development of memory CD8+ T cells. We found a reduction of effector memory and CD103+ tissue-resident memory (TRM) T cells in the lung of tumor-bearing NFATc1ΔCD4 mice, underlining an impaired cytotoxic T-cell response and a reduced TRM tissue-homing capacity. In CD4+ICOS+ T cells, programmed cell death 1 (PD-1) was induced in the draining lymph nodes of these mice and associated with lung tumor cell growth. Targeting PD-1 resulted in NFATc1 induction in CD4+ and CD8+ T cells in tumor-bearing mice and was associated with increased antitumor cytotoxic functions. This study reveals a role of NFATc1 in the activation and cytotoxic functions of T cells, in the development of memory CD8+ T-cell subsets, and in the regulation of T-cell exhaustion. These data underline the indispensability of NFATc1 for successful antitumor immune responses in patients with NSCLC.Significance: The multifaceted role of NFATc1 in the activation and function of T cells during lung cancer development makes it a critical participant in antitumor immune responses in patients with NSCLC. Cancer Res; 78(13); 3619-33. ©2018 AACR.
EVALuna2:34901

Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Benard, Alan; Podolska, Malgorzata; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bacterial airway infection; IRA B cells; mincle; necroptosis; pleural resident macrophages; pleural space

Short-chain fatty acids induced lung tumor cell death and increased peripheral blood CD4+ T cells in NSCLC and control patients ex vivo - Thome, Carolin; Tausche, Patrick; Hohenberger, Katja; Yang, Zuqin; Krammer, Susanne; Trufa, Denis; Sirbu, Horia; Schmidt, Joachim; Neurath-Finotto, Susetta (Frontiers in Immunology, 2024)
Background: Despite therapy advances, one of the leading causes of cancer deaths still remains lung cancer. To improve current treatments or prevent non-small cell lung cancer (NSCLC), the role of the nutrition in cancer onset and progression needs to be understood in more detail. While in colorectal cancer, the influence of local microbiota derived SCFAs have been well investigated, the influence of SCFA on lung cancer cells via peripheral blood immune system should be investigated more deeply. In this respect, nutrients absorbed via the gut might affect the tumor microenvironment (TME) and thus play an important role in tumor cell growth. Objective: This study focuses on the impact of the short-chain fatty acid (SCFA) Sodium Butyrate (SB), on lung cancer cell survival. We previously described a pro-tumoral role of glucose on A549 lung adenocarcinoma cell line. In this study, we wanted to know if SB would counteract the effect of glucose and thus cultured A549 and H520 in vitro with and without SB in the presence or absence of glucose and investigated how the treatment with SB affects the survival of lung cancer cells and its influence on immune cells fighting against lung cancer. Methods: In this study, we performed cell culture experiments with A549, H520 and NSCLC-patient-derived epithelial cells under different SB levels. To investigate the influence on the immune system, we performed in vitro culture of peripheral mononuclear blood cells (PBMC) from control, smoker and lung cancer patients with increasing SB concentrations. Results: To investigate the effect of SB on lung tumor cells, we first analyzed the effect of 6 different concentrations of SB on A549 cells at 48 and 72 hours cell culture. Here we found that, SB treatment reduced lung cancer cell survival in a concentration dependent manner. We next focused our deeper analysis on the two concentrations, which caused the maximal reduction in cell survival. Here, we observed that SB led to cell cycle arrest and induced early apoptosis in A549 lung cancer cells. The expression of cell cycle regulatory proteins and A549 lung cancer stem cell markers (CD90) was induced. Additionally, this study explored the role of interferon-gamma (IFN-γ) and its receptor (IFN-γ-R1) in combination with SB treatment, revealing that, although IFN-γ-R1 expression was increased, IFN-γ did not affect the efficacy of SB in reducing tumor cell viability. Furthermore, we examined the effects of SB on immune cells, specifically CD8+ T cells and natural killer (NK) cells from healthy individuals, smokers, and NSCLC patients. SB treatment resulted in a decreased production of IFN-γ and granzyme B in CD8+ T cells and NK cells. Moreover, SB induced IFN-γ-R1 in NK cells and CD4+ T cells in the absence of glucose both in PBMCs from controls and NSCLC subjects. Conclusion: Overall, this study highlights the potential of SB in inhibiting lung cancer cell growth, triggering apoptosis, inducing cell cycle arrest, and modulating immune responses by activating peripheral blood CD4+ T cells while selectively inducing IFN-γ-R1 in NK cells in peripheral blood and inhibiting peripheral blood CD8+ T cells and NK cells. Thus, understanding the mechanisms of action of SB in the TME and its influence on the immune system provide valuable insights of potentially considering SB as a candidate for adjunctive therapies in NSCLC.
CRIS-Team Scopus Importer:2024-05-03
Keywords: A549; glucose; IFN-γ-receptor; lung cancer; NSCLC; short chain fatty acids (SCFA); sodium butyrate; T cells

STAT1 deficiency supports PD-1/PD-L1 signaling resulting in dysfunctional TNFα mediated immune responses in a model of NSCLC - Friedrich, Juliane; Heim, Lisanne; Trufa, Denis; Sirbu, Horia; Rieker, Ralf; Neurath-Finotto, Susetta; Chiriac, Mircea-Teodor (Oncotarget, 2018)
In this study we described that Signal Transducer and Activator of Transcription 1 (STAT1) is a key point regulator of PD-1 in tumour infiltrating lymphocytes and PD-L1 in Tumour associated macrophages (TAM) in NSCLC. In our murine model of adenocarcinoma targeted deletion of Stat1 was found associated with enhanced tumour growth, impaired differentiation into M1-like macrophages from the bone marrow, the accumulation of tumor associated macrophages overexpressing PD-L1 and impaired T cell responses in the tumor microenvironment by affecting TNFα responses. In our human NSCLC patient cohort we found that loss of isoforms STAT1 α and STAT1β mRNA in the tumoural region of the lung correlates with increased tumor size in NSCLC patients. Therefore, STAT1 isoform regulation could be considered for future therapeutical strategies associated to current immune-checkpoint blockade therapy in NSCLC.
EVALuna2:207415

The role of Foxp3 and Tbet co-expressing Treg cells in lung carcinoma - Kachler, Katerina; Holzinger, Corinna; Trufa, Denis; Sirbu, Horia; Finotto, Susetta (OncoImmunology, 2018)
Despite the opposite roles of Tbet and Foxp3 in the immune system as well as in tumour biology, recent studies have demonstrated the presence of of CD4+ T cells, expressing both, Tbet and Foxp3. Although Tbet+Foxp3+ T cells are currently a subject of intense research, less is known about their biological function especially in cancer. Here we found a considerable accumulation of Tbet+Foxp3+CD4+ T cells, mediated by the immunosuppressive cytokine TGFβ in the lungs of tumour bearing mice. This is in line with previous studies, demonstrating the important role of TGFβ for the immunopathogenesis of cancer. By gathering results both in murine model and in human disease, we demonstrate that, the conversion of IFNγ producing anti-tumoral T-bet+Th1 CD4+ T cells into immunosuppressive Tbet and Foxp3-PD1 co-expressing regulatory cells could represent an additional important mechanism of TGFβ-mediated blockade of anti-tumour immunity.
EVALuna2:35735

The role of STAT3 (signal transducer and activator of transcription 3) in non-small cell lung cancer (NSCLC) - Heim, Lisanne; Andreev, Katerina; Balabko, Ljubov; Trufa, Denis; Sirbu, Horia; Hartmann, Arndt; Finotto, Susetta (2016)
EVALuna2:25984

Tumour immune evasion mechanism in non-small cell lung cancer by inducing Blimp-1 in CD4+CD25+Foxp-3+T regulatory cells - Neurath-Finotto, Susetta; Tausche, Patrick; Hohenberger, Katja; Neurath, Laura; Trufa, Denis; Geppert, Carol-Immanuel; Rieker, Ralf; Sirbu, Horia (JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2021-12-03